Analisa Jumlah Lilitan Magnetorheological Damper - Asngali, Bi; Prasetyo, Yuli; Amalia, Dwitya Solihati; Ubaidillah, Ubaidillah; Wangsa, Bhre (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Politeknik Pratama Mulia Surakarta, 2023)
Magnetorheological dampers with variations in the number of turns are simulated using the Finite Element Method Magnetics (FEMM) software to determine changes in the number of turns to the damping rate of the MR valve. The variations used are 90 turns, 180 turns, 270 turns, 365 turns, and 450 turns with a coil diameter of 0.4 mm, slit size of 0.1 mm, and an up and down serpentine MR valve design. The results of the simulation are the value of magnetic flux density (B) with Tesla units to predict the yield stress value of the MR fluid which is then used to calculate the value of the pressure difference and the value of the damping force. The Tesla value at each slit flow increases according to the input current value. the number of turns to the Tesla value is increasing. The results of calculating the value of the total pressure difference in the off-state conditions for the five variations are the same, namely 0.028330577 MPa. Meanwhile, the total pressure difference in the on-state condition, starting from a variation of 90 turns to a variation of 450 turns, always increases. The highest value of damping force is at current 2 A with a total of 90 turns worth 11007.66494 kN, 180 turns worth 14034.73989 kN, 270 turns worth 26535.68741 kN, and 365 turns worth 22227.83163 kN, except for variations in the number of turns 450 the winding is present at a current of 0.5 A with a value of 37492.11504 kN.